Kikuyu (Pennisetum clandestinun or Kikuyuocloa clandestina) silage fermented with three additives. - Boschini-Figueroa, Carlos; Pineda-Cordero, Luis (Agronomía Mesoamericana, 2015)
The objective of the study was to evaluate the characteristics of kikuyu grass silage with high humidity and the bromatologic quality when adding three different additives. These were added at three levels: molasses: 0, 2, and 4%, ground corn and citrus pulp: 5, 7 and 9% on a dry basis on the whole forage, fresh chopped and compacted in plastic bags. The experiment was conducted in 2010 at the El Pizote dairy farm, located in San Ramón, Tres Ríos, Cartago, Costa Rica. The experimental period lasted 77 days. Averages of 14.10%, 13.75%, 13.71% DM, 8.20%, 7.38%, 7.36% CP, 77.48%, 79.51%, 79.07% NDF, 39.22%, 40.12%, 39.68 % of FAD, 38.26%, 39.39%, 39.39% hemicellulose, 32.79%, 33.47%, 33.26% cellulose, 6.43%, 6.66%, 6.42% lignin, 2.23%, 1.89%, 2.04% EE and 11.53%, 11,74% , 11, 65% of total ash for silage with molasses, ground corn and citrus pulp respectively were obtained. Differences (p<0.05) were found in the amount of effluent according to the additive and the addition level. High humidity of kikuyu grass can cause that the effluents produce since the beginning until obtaining the maximum accumulation inside the bag, after 60 to 80 días of silage. That is why the bag has to be checked periodically and, if possible, drain the liquid effluents generated to avoid the process of deterioration.